ICT-INTEGRATED CLIL FOR DYSLEXIC LEARNERS: IMPROVING LEARNING AND COGNITIVE-MOTOR COORDINATION - Puvisha P; S. Selvalakshmi (International Journal of Research -GRANTHAALAYAH, 2026)
In present-day education, the language learning process is transformed into a multisensory process that involves auditory, visual, and physical interaction simultaneously. In this framework, Information and Communication Technology (ICT) integrated Content and Language Integrated Learning (CLIL) provides an innovative and effective pathways to support dyslexic learners who often faces challenges like confusion between similar letters, speech-motor fluency, weak phonological decoding, and problems in recognizing written patterns. The research investigates the potential of ICT-based CLIL activities (digital voice recording, interactive simulation, speech-to-text apps, etc.) to improve speech clarity, enhance multi-sensory engagement, and strengthen the mind-body connection. More specifically, the research explores how ICT CLIL activities improved speech accuracy through continuous listening and self-correction, enhance auditory-motor synchronization through immediate feedback, and develop ’eye-to-hand coordination’ through visual and motor engagement. This demonstrates how technology can be a resource for creating an inclusive, engaging, and meaningful learning space. The CLIL theory has the goals of fostering language and content learning at the same time while situations are contextualized and meaningful. The research highlights the benefits of task-structured ICT-CLIL learning, which not only provides feedback on verbal expression, visual tracking, and listening accuracy, but also helps dyslexic students to independently learn, raise their confidence, improve coordination, and create a positive atmosphere within the classroom. Additionally, it can assist in developing skills in language and content knowledge simultaneously.